Pelatihan Pembibitan dan Pembuatan Produk Minuman Jahe Bagi Kelompok Wanita Tani (KWT) “Dewi Sri” Desa Kemetul Kecamatan Susukan - Wahyudi, Avian Tri; Prasetyo, Damar Adi; Vifta, Rissa Laila; Pujiastuti, Anasthasia; Santoso, Wingit (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Ginger is a one of rhizome herbal plant that has many health benefits. Consumption of ginger both directly and through the manufacture of ginger-based products has also increased during the pandemic and after the pandemic. The utilization of yard land that is less than optimal and the low selling of ginger are the main problems faced by the Women Farmer Group "Dewi Sri" in Kemetul Village, which are the background for the implementation of Community Service activities carried out by the Himafarsi Service Team, Ngudi Waluyo University. The activity was carried out through Training on Breeding and Making Ginger Drink Products with the target partner of the Women Farmers Group (KWT) â€œDewi Sriâ€ Kemetul Village. The method of implementing the program is done offline and online. The results of the Service activities can be seen through the success indicators which show an increase in participants' knowledge by 64%. Community Service Activities have resulted in activity outputs in the form of ginger seeds in polybags on the pilot land and beverage products in the form of instant ginger powder with the basic ingredients of Red Ginger and Emprit Ginger which have been through hedonic tests by respondents. ABSTRAKJahe merupakan salah satu tanaman herbal jenis rimpang yang memiliki banyak khasiat bagi kesehatan. Konsumsi terhadap jahe baik secara langsung maupun melalui pembuatan produk berbahan dasar jahe juga meningkat selama pandemi berlangsung maupun pasca pandemi. Pemanfaatan lahan pekarangan yang kurang maksimal serta rendahnya harga jual jahe merupakan permasalahan utama yang dihadapi oleh Kelompok Wanita Tani Dewi Sri Desa Kemetul menjadi latar belakang pelaksanaan kegiatan Pengabdian kepada Masyarakat yang dilaksanakan oleh Tim Pengabdian Himafarsi Universitas Ngudi Waluyo. Kegiatan dilakukan melalui Pelatihan Pembibitan dan Pembuatan Produk Minuman Jahe dengan mitra sasaran Kelompok Wanita Tani (KWT) Dewi Sri Desa Kemetul. Metode pelaksanaan program dilakukan secara offline dan online. Hasil kegiatan Pengabdian dapat dilihat melalui indikator keberhasilan yang menunjukkan peningkatan pengetahuan peserta sebesar 64%. Kegiatan Pengabdian kepada Masyarakat telah menghasilkan output kegiatan berupa bibit jahe dalam polybag pada lahan percontohan dan produk minuman berupa serbuk jahe instan dengan bahan dasar Jahe Merah dan Jahe Emprit yang telah melalui uji hedonik oleh responden.